THE EFFECT OF PROFITABILITY, CAPITAL STRUCTURE, FIRM SIZE, AND ASSET GROWTH ON FIRM VALUE - Boenyamin, Angelina William; Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to collect empirical data on the effect of profitability, capital structure, firm size, and asset growth on firm value in banking companies listed on the Indonesia Stock Exchange in 2018 – 2020. This study uses a purposive sampling method with 31 banking companies listed on the Indonesian Stock Exchange. The Microsoft Excel application was used to enter and calculate the study's data, and the Eviews 12 tool was used to process it. The results of this study indicate that firm size significantly positively affects firm value while profitability, capital structure, and asset growth have no significant effect on firm value.